Feasibility of Clinicians Aligning Health Care with Patient Priorities in Geriatrics Ambulatory Care. Issue 9 (20th July 2020) - Freytag, Jennifer; Dindo, Lilian; Catic, Angela; Johnson, Adrienne L.; Bush Amspoker, Amber; Gravier, Anna; Dawson, Darius B.; Tinetti, Mary E.; Naik, Aanand D.
Abstract : BACKGROUND/OBJECTIVES: Aligning healthcare decisions with patients' priorities may improve care for older adults with multiple chronic conditions (MCCs). We conducted a pilot study to assess the feasibility of identifying patient priorities in routine geriatrics care and to compare clinicians' recommendations for patients who did or did not have their priorities identified. DESIGN: Retrospective chart review. SETTING: Veterans Administration Medical Center Geriatrics Clinic. PARTICIPANTS: Older adults with MCCs receiving Patient Priorities Care (PPC; n = 35) were matched with patients receiving usual care (UC; n = 35). Both PPC and UC patients were cared for by three primary care providers (PCPs) in an ambulatory geriatric clinic. INTERVENTION: In the PPC group, a clinician facilitator met with each patient to identify their healthcare priorities and transmitted patients' priorities in the electronic health record (EHR). Trained PCPs then sought to align healthcare decisions with patients' priorities. In the UC group, patients received usual care from the same PCPs. MEASUREMENTS: We matched patients by clinician seen, patient's age, number of active conditions, medications, hospitalizations, functional status, and prior hospitalizations. EHRs were reviewed to identify care decisions including medications added or stopped, referrals and consults added or avoided, referrals to community services and supports, self‐management activities added or avoided, and total number of changes to care. Mean differences in recommended care between PPC and UC patients from the same PCPs were examined. RESULTS: Clinician facilitators could identify patient priorities during routine clinic encounters. Compared with patients in the UC group, those in the PPC group had, on average, fewer medications added ( P = .05), more referrals to community services and supports ( P = .03), and more priorities‐aligned self‐management tasks added ( P = .005). CONCLUSION: These findings support the feasibility of identifying and documenting patient priorities during routine encounters. Results also suggest that clinicians use patient priorities in recommending care.